0
$\begingroup$

I am facing difficulty in employing Cauchy's general principle of convergence to prove that a sequence is convergent.

Let's take this example:

Let $x_1 = 2$, and $x_{n+1} = \sqrt{x_n+20}$, for $n=1,2,3,\dots$
Prove that the sequence {$x_n$} converges.

I solved this using monotone convergence theorem. Using induction, it can be proved that the sequence is increasing and is bounded above by $5$. Thus, it is convergent.

But how do I prove this using Cauchy's principle, which states that, for each $\epsilon > 0$ there exists a positive integer $m$ such that

$|S_{n+p}-S_n|<\epsilon$, $\forall$ $n\geq m $ and $p\geq1$, $\{S_n\}$ being the sequence.

$\endgroup$
1
$\begingroup$

let $x_{n+1}>x_{n}$ then

$x_{n+1}+20 >x_n+20$ $\Rightarrow$ $\sqrt{x_{n+1}+20}=x_{n+2}>\sqrt{x_n+20}=x_{n+1}$

and we know that $x_2 > x_1$ so $x_n$ is increasing

also, note that $2 \leq x_n < 5$ $\Rightarrow$ $2\sqrt{22} \leq\sqrt{x_a+20}+\sqrt{x_b+20}<10$ hence $\frac{1}{\sqrt{x_a+20}+\sqrt{x_b+20}}>8$

$x_{n+p}-x_n = \sqrt{x_{n+p-1}+20}-\sqrt{x_{n-1}+20}= \frac{x_{n+p-1}-x_{n-1}}{\sqrt{x_{n+p-1}+20}+\sqrt{x_{n-1}+20}}=\frac{\sqrt{x_{n+p-2}+20}-\sqrt{x_{n-2}+20}}{\sqrt{x_{n+p-1}+20}+\sqrt{x_{n-1}+20}}$

$\frac{\sqrt{x_{n+p-2}+20}-\sqrt{x_{n-2}+20}}{\sqrt{x_{n+p-1}+20}+\sqrt{x_{n-1}+20}}=\frac{x_{p+1}-\sqrt{22}}{(\sqrt{x_{n+p-1}+20}+\sqrt{x_{n-1}+20})...(\sqrt{x_{p+1}+20}+\sqrt{22})}< \frac{x_{p+1}-\sqrt{22}}{8^{n-2}}$

$\frac{x_{p+1}-\sqrt{22}}{8^{n-2}}<\frac{5-\sqrt{22}}{8^{n-2}}< \epsilon$ $\Rightarrow$ $\frac{1}{8^{n-2}}<\frac{\epsilon}{5-\sqrt{22}}$ and we know there exists and $m$ such that

$m > n \Rightarrow |\frac{1}{8^{n-2}}-0|=\frac{1}{8^{n-2}}<\frac{\epsilon}{5-\sqrt{22}}$

so $x_n$ is convergent

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.